Environmental management and stewardship practices in Antarctic science and tourism: do they align with environmental concerns? - Cajiao, Daniela; Tejedo, Pablo; Amelung, Bas; Benayas, Javier; Lamers, Machiel (Polar research, 2025)
In the Antarctic Peninsula, tourism and science operations are interconnected and overlap spatially and temporally, sharing practices aimed at reducing and mitigating the human footprint. Guided by the concepts of environmental management and environmental stewardship, we examined how these environmental practices address the various types of environmental impacts generated by these operations. For this, we categorized the environmental impacts identified in the literature and conducted an expert survey to assess which of these impact categories are the most concerning. Then, we consulted the Inspection Reports of the Antarctic Treaty Consultative Parties, tour operators’ annual reports and documents from the International Association of Antarctica Tour Operators to capture environmental management and stewardship practices. Finally, we evaluated to what extent these practices address the categories of impacts. We identified 68 environmental practices for science and 63 for tourism operations. We classified them into nine categories, which range from mitigating soil and water contamination to limiting landscape modifications, minimizing impacts on flora, fauna and ecosystems and reducing greenhouse gas emissions. We identified a significant number of practices addressing local and specific impact categories. In contrast, a smaller number of practices were identified for the impacts that are most concerning in terms of their geographical scale, duration and severity, according to our experts’ survey. We discuss that the number of practices does not reflect their effectiveness, and the positive influence of some practices in building formal management instruments. Greater collaboration among stakeholders will improve the protection of the Antarctic continent.